Test sample preparation method and test sample preparation system
By preparing and testing standard slurries with different water-adhesive ratios in the field of building materials research, establishing their functional relationships, calculating the formulated water-adhesive ratio, and preparing regular-shaped micro-gel gelling material samples, the samples in the prior art were solved The problems of irregular shapes and insufficient imaging resolution achieve efficient X-ray nanoCT scanning test.
Patent Information
- Application Number
- CN201910582745.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-06-28
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2039-06-28
AI Technical Summary
In the field of building materials research, there are fewer methods for preparing gelled material samples suitable for high-resolution nano X-ray imaging technology. The existing methods are difficult to meet the requirements of high-resolution imaging, and the sample shape is irregular, which affects the imaging results.
By preparing multiple standard slurries with different initial water-adhesive ratios, and testing the actual water-adhesive ratio in a micron-level sample preparation mold, establishing a functional relationship between the actual water-adhesive ratio and the initial water-adhesive ratio, calculating the prepared water-adhesive ratio, and preparing A micron-scale test sample with regular shape was produced.
It realizes the preparation of regular-shaped micro-gel material samples, which are suitable for X-ray nano-CT scanning testing, improves imaging resolution and signal-to-noise ratio and reduces imaging errors.
Smart Images

Figure CN110333126B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of gelling materials, in particular to a test sample preparation method and a test sample preparation system. Background Art
[0002] X-ray 3D imaging technology has long been widely used in materials, biology, medicine and other fields. However, in the field of materials research, there is still no unified and effective method for sample preparation for high-resolution nano X-ray imaging technology. Especially in the field of building materials research, there is even less research on the preparation method of cementitious material samples suitable for high-resolution nano X-ray imaging technology.
[0003] The main reason is that the prepared samples are difficult to meet the basic requirements of high-resolution nano-X-ray imaging technology. According to the imaging principle of X-rays, compared with micron X-ray imaging technology (using a light source voltage of 40kV to 150kV), improving the resolution of imaging means that a relatively low energy intensity light source needs to be selected. The X-ray energy for nano-resolution generally uses 5.4keV, Cr-Kα or 8.0keV, Cu-Kα, which reduces the unit X-ray radiation quantum amount and requires an increase in exposure time and a reduction in the working distance between the sample and the light source, thereby increasing the imaging contrast and improving the resolution. However, the imaging range (FOV, Field of view) of the device will be reduced accordingly and the sample thickness that the device can image will be reduced. If the sample size is large, the part beyond the imaging range will not be scanned and imaged by the X-rays, resulting in false images in the three-dimensional reconstruction results. X-rays with low energy intensity cannot penetrate the sample and are detected and imaged by the detector. Therefore, for commercially available X-ray nano-CT scanning equipment, according to the description of the X-ray attenuation coefficient by the Beer-Lambert law, in order to achieve nanometer-level resolution imaging of building cementitious materials, reduce three-dimensional reconstruction imaging errors and improve the signal-to-noise ratio, it is necessary to prepare micrometer-level cementitious material samples.
[0004] The simplest traditional sample preparation method is to prepare micron-sized samples by manual hammering and cutting, and place the samples on the needle tip to complete the sample preparation steps. However, this method is easy to introduce artificial deformation or even cracks to the samples, and the sample shape and size are random and irregular. In terms of sample preparation of cementitious materials, some studies have proposed using gold foil to obtain it by clamping and then cutting, but the sample prepared by this method has an irregular shape, which is not conducive to imaging; another study has also proposed another method for preparing micron-sized samples for X-ray nano-CT scanning tests. This method directly places cementitious material powder particles on the tip of a tungsten needle, and a container containing a solution is glued to the side of the tungsten needle, and the whole is placed in a larger polymer tube to construct a hydration environment with constant humidity, but this method also has the problem of irregular shapes of the prepared samples. Summary of the invention
[0005] Based on this, it is necessary to provide a method for preparing a test sample that can make the shape of the test sample regular and can be used for X-ray nano CT scanning test.
[0006] In addition, a test sample preparation system is also provided.
[0007] A method for preparing a test sample comprises the following steps:
[0008] A plurality of standard slurries with different initial water-to-binder ratios are prepared using raw materials for preparing test samples, wherein the test samples are gelling materials and the raw materials include solid raw materials and solvents;
[0009] Placing a plurality of standard slurries with different initial water-binder ratios in a plurality of sample preparation molds respectively, and then testing the actual water-binder ratio of the standard slurries in each of the sample preparation molds, wherein the inner diameter of the sample preparation mold is in the micrometer order;
[0010] According to the plurality of actual water-binder ratios and the plurality of initial water-binder ratios, establishing a functional relationship between the actual water-binder ratio and the initial water-binder ratio;
[0011] Calculating the water-binder ratio of the test sample according to the functional relationship and the water-binder ratio of the test sample;
[0012] According to the water-binder ratio, preparing the raw materials into a sample slurry; and
[0013] The sample slurry is placed in the sample preparation mold to obtain the test sample.
[0014] In one embodiment, the test sample is a sample for X-ray nano-CT scanning test.
[0015] In one embodiment, the inner diameter of the sample preparation mold is smaller than the maximum thickness of the test sample that can be tested by the X-ray nano-CT scanning test.
[0016] In one embodiment, before the step of placing the plurality of standard slurries with different initial water-binder ratios in a plurality of sample preparation molds, a step of determining the maximum thickness of the test sample that can be tested by the X-ray nano CT scanning test is also included, and the step of determining the maximum thickness includes:
[0017] According to the density and effective atomic number of the solid raw material, and the X-ray energy intensity used by the light source of the X-ray nano-CT scanning test, according to the formula Calculating the X-ray attenuation coefficient of the solid raw material, wherein μ represents the X-ray attenuation coefficient, ρ represents the density, Z represents the effective atomic number, E represents the X-ray energy intensity, and K is a constant;
[0018] According to the formula φ=φ 0 exp(-μD), to obtain the maximum thickness of the test sample that can be tested by the X-ray nano-CT scanning test, where φ represents the intensity of the emitted photons, φ 0 represents the incident photon intensity, φ and φ 0 The ratio is greater than or equal to l / e, and D is the thickness of the test sample.
[0019] In one embodiment, the step of establishing a functional relationship between the actual water-binder ratio and the initial water-binder ratio according to the multiple actual water-binder ratios and the multiple initial water-binder ratios comprises:
[0020] According to the plurality of actual water-binder ratios and the plurality of initial water-binder ratios, establishing a relationship curve between the actual water-binder ratio and the initial water-binder ratio;
[0021] The relationship curve is linearly fitted to obtain the functional relationship between the actual water-binder ratio and the initial water-binder ratio.
[0022] In one embodiment, in the step of testing the actual water-binder ratio of the standard slurry in each of the sample preparation molds, a thermogravimetric method is used to test the actual water-binder ratio of the standard slurry in each of the sample preparation molds.
[0023] In one of the embodiments, in the step of placing the multiple standard slurries with different initial water-to-binder ratios in multiple sample preparation molds respectively, vacuum extraction is performed so that the multiple standard slurries with different initial water-to-binder ratios are placed in multiple sample preparation molds respectively, and the vacuum degree during the vacuum extraction process is the same.
[0024] In one embodiment, the material of the sample preparation mold is a polymer.
[0025] A test sample preparation system, comprising:
[0026] A batching device capable of holding slurry;
[0027] A sample preparation mold, capable of holding the slurry, and the inner diameter of the sample preparation mold is micron-level;
[0028] A material transfer device capable of transferring the slurry in the batching device to the sample preparation mold; and
[0029] The testing device is capable of testing the water-binder ratio of the slurry in the sample preparation mold.
[0030] In one of the embodiments, the sample making mold can be connected to the batching device, and the material transfer device includes a connecting unit and a power unit. The connecting unit can be connected to the sample making mold, and the power unit can be connected to the connecting unit, so that the slurry in the batching device can be extracted into the sample making mold.
[0031] In one embodiment, the sample preparation mold has a feed port and an exhaust port, the feed port can be connected to the batching device, the connecting unit includes a micro-injector and a connector detachably connected to the micro-injector, the micro-injector can be connected to the power unit, the connector can be connected to the exhaust port, and when the connector is connected to the exhaust port, the connector is sealed and connected to the sample preparation mold, so that the slurry in the batching device can be extracted into the sample preparation mold.
[0032] In one embodiment, the power unit comprises a vacuum pump, and the vacuum pump can be communicated with the connection unit so that the slurry in the batching device can be drawn into the sample preparation mold.
[0033] In the preparation method of the test sample, since the inner diameter of the sample preparation mold used is in the micron level, the size of the obtained test sample is in the micron level, and the shape of the test sample is regular, which can be used for X-ray nano CT scanning test. And the preparation method of the test sample first establishes a functional relationship between the actual water-binder ratio and the initial water-binder ratio through the initial water-binder ratio of multiple standard slurries and the actual water-binder ratio, so that the water-binder ratio of the sample slurry can be calculated according to the functional relationship and the water-binder ratio of the test sample to be prepared, so as to prepare the sample slurry and place it in the sample preparation mold to obtain the test sample of the above water-binder ratio. The water-binder ratio of the test sample has a greater impact on the X-ray nano CT scanning test, and only the water-binder ratio of the known test sample can make the test sample used for the X-ray nano CT scanning test. Therefore, the preparation method of the test sample can make the size of the prepared test sample micron-level, regular in shape, and can be used in the X-ray nano CT scanning test. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 is a process flow chart of a method for preparing a test sample according to an embodiment;
[0035] Figure 2 is a schematic structural diagram of a test sample preparation system according to an embodiment;
[0036] Figure 3 This is a curve diagram showing the relationship between the attenuation length of X-rays penetrating the sample and the X-ray energy when the main components of the cement standard in Example 1 are tricalcium silicate, dicalcium silicate, and tricalcium aluminate;
[0037] Figure 4 The graph is a relationship between the X-ray penetration rate and the X-ray energy when the thickness of the main components of the cement standard product in Example 1, tricalcium silicate, dicalcium silicate, and tricalcium aluminate, is 65 μm;
[0038] Figure 5 is a curve diagram showing the relationship between the attenuation length of the sample making mold and the X-ray energy when the material of the sample making mold in Example 1 is PEEK;
[0039] Figure 6 The relationship curve between the transmittance of the sample preparation mold and the X-ray energy is shown in Example 1 when the material of the sample preparation mold is PEEK and the total diameter is 800 μm;
[0040] Figure 7 is a curve diagram showing the relationship between the actual water-binder ratio and the initial water-binder ratio in Example 1;
[0041] FIG8(a) is a position diagram of the nanoindentation test of sample A in Example 1, FIG8(b) is a data distribution diagram of the nanoindentation test of sample A, and FIG8(c) is a Gaussian fitting result diagram of the large sample data after the nanoindentation test of sample A;
[0042] FIG9(a) is a position diagram of the nanoindentation test of sample B in Example 1, FIG9(b) is a data distribution diagram of the nanoindentation test of sample B, and FIG9(c) is a Gaussian fitting result diagram of the large sample data processed by the nanoindentation test of sample B (including the sample preparation mold);
[0043] FIG10( a ) is a three-dimensionally reconstructed image of sample B in Example 1, and FIG10( b ), FIG10( c ) and FIG10( d ) are two-dimensional slice images in three different directions of the three-dimensionally reconstructed image of sample B in FIG10( a );
[0044] FIG. 11( a ) and FIG. 11( b ) are 3D images of sample B in Example 1 after three-dimensional reconstruction to different degrees. DETAILED DESCRIPTION
[0045] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below in conjunction with the specific embodiments. Preferred embodiments of the present invention are provided in the specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0046] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0047] It should be noted that there is no special regulation on the mixing time when the sample slurry is stirred in this article, and the mixing method well known to those skilled in the art can be adopted.
[0048] There is no special provision for the X-ray nano-CT scanning device in this article, and an X-ray nano-CT scanning device well known to those skilled in the art can be used.
[0049] See also Figure 1 A method for preparing a test sample according to an embodiment of the present invention comprises the following steps:
[0050] Step S110: preparing a plurality of standard slurries with different initial water-to-binder ratios using raw materials for preparing test samples, wherein the test samples are gelling materials and the raw materials include solid raw materials and solvents.
[0051] The test sample is a sample for X-ray nano-CT scanning test. The initial water-to-binder ratio refers to the weight ratio of the solvent to the solid raw material during the preparation process. Specifically, in this embodiment, the solvent is water. The solid raw material can be tricalcium silicate, dicalcium silicate, etc.
[0052] Step S120: placing a plurality of standard slurries with different initial water-binder ratios in a plurality of sample making molds respectively, and then testing the actual water-binder ratio of the standard slurry in each sample making mold, wherein the inner diameter of the sample making mold is in micrometer order.
[0053] Specifically, in the step of placing multiple standard slurries with different initial water-binder ratios in multiple sample preparation molds, multiple standard slurries with different initial water-binder ratios are placed in multiple sample preparation molds by vacuum extraction, and the vacuum degree during the vacuum extraction process is the same. In step S120, multiple standard slurries are introduced into the sample preparation mold by vacuum extraction because the inner diameter of the sample preparation mold is micron-level. If direct extraction is adopted, it is difficult to extract, and the extraction time is long. The long extraction time will cause the solidification of the standard slurry, etc., and it is impossible to continue to extract into the sample preparation mold. Therefore, vacuum extraction is adopted to allow the standard slurry to enter the sample preparation mold. Specifically, the vacuum extraction time is 3 minutes.
[0054] Furthermore, the vacuum degrees in the steps of vacuum extraction of multiple standard slurries with different initial water-binder ratios into multiple sample preparation molds are made the same. This is because, under the same initial water-binder ratio, different vacuum degrees will result in different actual water-binder ratios of the obtained standard samples. Therefore, when studying the relationship between the actual water-binder ratio and the initial water-binder ratio, the vacuum degrees are set to be the same, so that the actual water-binder ratio is only related to the initial water-binder ratio.
[0055] The actual water-to-binder ratio refers to the weight ratio of water in the standard slurry to the solid raw material in the sample making mold.
[0056] Specifically, in the step of testing the actual water-binder ratio of the standard slurry in each sample preparation mold, a thermogravimetric method is used to test the actual water-binder ratio of the standard slurry in each sample preparation mold.
[0057] Further, the steps of testing the actual water-binder ratio of each standard slurry by the thermogravimetric method include:
[0058] Testing the solid raw material to obtain a benchmark weight loss rate curve of the solid raw material;
[0059] Testing the sample making mold to obtain a reference weight loss rate curve of the sample making mold;
[0060] The standard sample is tested to obtain a weight loss rate curve of the standard sample, and the weight loss rate curve of the standard sample is corrected according to a reference weight loss rate curve of the solid raw material and a reference weight loss rate curve of the sample preparation mold to obtain a corrected weight loss rate curve of the standard sample;
[0061] According to the weight loss rate curve after correction of the standard sample, the actual water-binder ratio of the standard sample is obtained.
[0062] Furthermore, a thermogravimetric analysis device was used for testing during the above test process.
[0063] Specifically, the material of the sample preparation mold is a polymer. Further, the polymer is polyimide or polyetheretherketone. Since the X-ray attenuation coefficient of the polymer can be almost negligible, the sample preparation mold made of the polymer material is selected as the container for the test sample, so that when the test sample is used for testing, the influence of the sample preparation mold on the test result can be almost negligible.
[0064] The sample preparation mold is cylindrical. The inner diameter of the sample preparation mold is micrometer-level, which can make the thickness of the obtained test sample micrometer-level and regular in shape. The sample preparation mold is cylindrical. When used for X-ray nano-CT scanning test, it scans in three-dimensional directions to reconstruct a three-dimensional image of the test sample.
[0065] Furthermore, the inner diameter of the sample preparation mold is smaller than the maximum thickness of the test sample of the X-ray nano-CT scanning test. The maximum thickness refers to the maximum distance that the X-ray is incident from the test sample and can be emitted from the test sample during the X-ray nano-CT scanning test. The maximum thickness of the test sample of the X-ray nano-CT scanning test is in the micron level. Specifically, before step S120, it also includes a step of determining the maximum thickness of the test sample that can be tested by the X-ray nano-CT scanning test. Specifically, the step of determining the maximum thickness includes:
[0066] According to the density and effective atomic number of the solid raw material and the X-ray energy intensity used by the light source of the X-ray nano-CT scanning test, the formula The X-ray attenuation coefficient of the solid raw material is calculated, where μ represents the X-ray attenuation coefficient, ρ represents the density, Z represents the effective atomic number, E represents the X-ray energy intensity, and K is a constant;
[0067] According to the formula φ=φ 0 exp(-μD), the maximum thickness of the test sample that can be tested by X-ray nano-CT scanning test is obtained, where φ represents the intensity of the emitted photons, φ 0 represents the incident photon intensity, φ and φ 0 The ratio is greater than or equal to 1 / e, and D is the thickness of the test sample.
[0068] Among them, when the sample is a compound composed of multiple atoms, the effective atomic number is used, and the calculation basis of the effective atomic number is as follows:
[0069] In the formula, f i is the weight ratio of the number of extranuclear electrons of the ith atom to the total number of extranuclear electrons in the chemical formula of the compound, Z i is the atomic number of the ith atom.
[0070] When the solid raw material of the test sample is a plurality of compounds, the X-ray attenuation coefficient of each solid raw material compound is calculated respectively, and the largest X-ray attenuation coefficient among the X-ray attenuation coefficients of the plurality of solid raw material compounds is used to calculate the maximum thickness.
[0071] In this paper, the formula It can be simplified by μ / ρ=a+b×(Z^3.8 / E^3.2). For commonly used solid raw materials, the K value is about 1.4×10 -3 .
[0072] Furthermore, the inner diameter of the sample preparation mold is set to be smaller than the maximum thickness of the sample that can be tested by the X-ray nano-CT scanning test, so that the test sample can be placed in the sample preparation mold. When used for X-ray nano-CT scanning, the X-rays of the X-ray nano-CT scanning test can penetrate the test sample, and the test sample all falls within the imaging range of the X-ray nano-CT scanning, thereby enabling the nanoscale pore structure, material composition, etc. of the test sample to be clearly studied.
[0073] Commonly used X-ray nano-CT scanning equipment has X-ray monochromatic light source energies of 5.4keV, 6.4keV and 8.0keV. When the X-ray monochromatic light source energy is 8keV, for ordinary Portland cement whose main components are tricalcium silicate, dicalcium silicate and tricalcium aluminate, assuming the porosity is zero, the cross-sectional size of ordinary Portland cement that can be tested by the X-ray nano-CT scanning equipment is 60μm to 150μm.
[0074] Step S130: establishing a functional relationship between the actual water-binder ratio and the initial water-binder ratio according to the multiple actual water-binder ratios and the multiple initial water-binder ratios.
[0075] Specifically, step S130 includes:
[0076] According to a plurality of actual water-binder ratios and a plurality of initial water-binder ratios, a relationship curve between the actual water-binder ratio and the initial water-binder ratio is established;
[0077] The relationship curve was linearly fitted to establish the functional relationship between the actual water-binder ratio and the initial water-binder ratio.
[0078] By establishing a functional relationship between the actual water-binder ratio and the initial water-binder ratio, it is easy to achieve controllable water-binder ratio of the prepared test sample. For example, to prepare a test sample with a certain target water-binder ratio, the prepared water-binder ratio corresponding to the target water-binder ratio can be obtained based on the relationship curve between the actual water-binder ratio and the initial water-binder ratio, and then the raw materials for preparing the test sample are prepared into the prepared water-binder ratio, and then placed in a sample preparation mold to obtain a test sample with the target water-binder ratio, thereby achieving controllable water-binder ratio of the prepared test sample.
[0079] Step S140: Calculate the water-binder ratio of the test sample according to the functional relationship and the water-binder ratio of the test sample.
[0080] The water-to-binder ratio is the weight ratio of the solvent to the solid raw material during the preparation process. The water-to-binder ratio of the test sample can be obtained through step S140.
[0081] Step S150: preparing the raw materials into a sample slurry according to the water-binder ratio.
[0082] Specifically, the solid raw material and the solvent are prepared into a sample slurry according to the above-mentioned water-to-binder ratio.
[0083] Step S160: placing the sample slurry in a sample preparation mold to obtain a test sample.
[0084] The sample slurry is placed in the sample preparation mold by vacuum extraction. Further, the vacuum degree in the vacuum extraction process is the same as the vacuum degree in the vacuum extraction process in step S120. This is because the actual water-binder ratio obtained has a different functional relationship with the initial water-binder ratio due to different vacuum degrees. Only under the same vacuum degree can the water-binder ratio of the test sample be obtained based on the above functional relationship and water-binder ratio.
[0085] By using the test sample preparation method, the obtained test sample can be made into a micron-sized sample with a regular shape and a controllable water-to-binder ratio.
[0086] Regarding the preparation of samples for X-ray nano-CT scanning tests, some researchers have proposed a preparation method that uses focused ion beam technology (FIB), which is suitable for cutting and forming most samples and can accurately prepare samples by bombarding with ion beams at nanometer precision. However, this method is expensive and only suitable for samples with a certain strength. It is not suitable for gelled samples that are still in the early stages of hydration reactions, nor for powder samples. Another study proposed a method for preparing micron-sized samples suitable for X-ray nano-CT scanning tests. This method uses lasers to grind rotating cylindrical samples, and the size can reach 30μm. However, like FIB, it is only suitable for samples with a certain strength, and the laser will leave deformation marks on the surface of the prepared sample, affecting the result judgment. The study pointed out that the affected range of lithium battery cathode materials is 10μm. The size of the test samples obtained by the traditional method for preparing test samples for X-ray nano-CT scanning tests is irregular, which is easy to cause deformation on the surface of the test samples, and the applicability of the preparation method is limited to a certain extent.
[0087] The above test sample preparation method has at least the following advantages:
[0088] (1) The above test sample preparation method can make the obtained test sample have a size of micrometer level and a regular shape.
[0089] (2) The test sample prepared by the above test sample preparation method can be used in X-ray nano-CT scanning test to analyze the nano-scale structure, material composition, etc. of the test sample.
[0090] (3) The above test sample preparation method has good repeatability.
[0091] (4) The above test sample preparation method will not leave any deformation marks on the surface of the test sample, and will not affect the test results of the obtained test sample during the test.
[0092] (5) The above test sample preparation method can be used for gelled samples in the early stage of hydration reaction and has no limitation on the strength of the samples.
[0093] See also Figure 2 A test sample preparation system 10 according to one embodiment includes a batching device 100, a sample preparation mold 200, a material transfer device 300 and a testing device (not shown in the figure).
[0094] The batching device 100 can contain slurry. Specifically, the slurry includes sample slurry and standard slurry. The sample slurry and the standard slurry are prepared from the raw materials for preparing the test sample. There are multiple standard slurries, and the initial water-binder ratios of the multiple standard slurries are different.
[0095] Specifically, the batching device 100 may be a stirring tank.
[0096] The sample preparation mold 200 can hold the slurry. Specifically, the inner diameter of the sample preparation mold 200 is micrometer level. The sample preparation mold 200 is cylindrical.
[0097] The sample preparation mold 200 is set to be cylindrical, and the inner diameter of the sample preparation mold 200 is in the micron level, so that the size of the obtained test sample can be in the micron level and the shape is regular, and can be used for X-ray nano-CT scanning test. When used for X-ray nano-CT scanning test, it can scan in three directions to reconstruct a three-dimensional image of the test sample.
[0098] Furthermore, the inner diameter of the sample preparation mold 200 is smaller than the maximum thickness of the test sample that can be tested by the X-ray nano-CT scanning test, wherein the maximum thickness refers to the maximum distance that the X-ray enters the test sample and can be emitted from the test sample during the X-ray nano-CT scanning test.
[0099] The sample preparation mold 200 is a polymer mold. Specifically, the sample preparation mold 200 is a polyimide mold or a polyetheretherketone mold. The X-ray attenuation coefficient of the sample preparation mold 200 of the above material is almost negligible, so that when the prepared test sample is used for X-ray nano-CT scanning test, the sample preparation mold 200 will not affect the test result.
[0100] Further, the sample preparation mold 200 can be communicated with the batching device 100. Specifically, the sample preparation mold 200 has a feed port and an air extraction port, and the feed port can be communicated with the batching device 100.
[0101] The material transfer device 300 can transfer the slurry in the batching device 100 to the sample preparation mold 200. Specifically, the material transfer device 300 can transfer the slurry in the batching device 100 to the sample preparation mold 200 by extraction or suction. Further, in this embodiment, the material transfer device 300 can transfer the slurry in the batching device 100 to the sample preparation mold 200 by extraction. It can be understood that in other embodiments, the material transfer device 300 can also transfer the slurry in the batching device 100 to the sample preparation mold 200 by suction.
[0102] Specifically, the material transfer device 300 includes a connection unit 310 and a power unit 320 . The connection unit 310 can be communicated with the sample preparation mold 200 , and the connection unit 310 can be communicated with the power unit 320 , so that the slurry in the batching device 100 can be extracted into the sample preparation mold 200 .
[0103] The connection unit 310 includes a micro-injector 312 and a connector 314 detachably connected to the micro-injector 312. The micro-injector 312 can be connected to the power unit 320. The connector 314 can be connected to the air suction port, and when the connector 314 is connected to the air suction port, the connector 314 is sealed and connected to the sample preparation mold 200, so that the slurry in the batching device 100 can be extracted into the sample preparation mold 200. Since the inner diameter of the sample preparation mold 200 is micron-level, it cannot be directly connected to the power unit 320. Therefore, the sample preparation mold 200 is first connected to the micro-injector 312, and then connected to the power unit 320.
[0104] Specifically, the connector 314 includes a Luer connector 3142 and a split connector 3144. The Luer connector 3142 can be detachably connected to the micro-injector 312. The split connector 3144 can be detachably connected to the Luer connector 3142, and the split connector 3144 can be connected to the air suction port of the sample preparation mold 200. Further, the connector 314 also includes a blade ring, which can be detachably connected to the Luer connector 3142, and the blade ring can be detachably connected to the split connector 3144, so that the Luer connector 3142 can be detachably connected to the micro-injector 312. The sample preparation mold 200 is connected to the micro-injector 312 through the above-mentioned connector 314, so that the sample preparation mold 200 can be sealed and connected to the micro-injector 312. It can be understood that the connector 314 is not limited to the above-mentioned connector, and any connector 314 that can seal the sample preparation mold 200 and the micro-injector 312 can be used as the connector 314 of this embodiment.
[0105] Further, the connecting unit 320 also includes a pipeline 316. The micro-injector 312 is connected to the power unit 320 through the pipeline 316. In this embodiment, the pipeline 316 is a hard silicone tube. It is understood that in other embodiments, the pipeline 316 can also be other pipelines 316, and any pipeline 316 that can connect the micro-injector 312 and the power unit 320 can be used as the pipeline 316 of this embodiment.
[0106] The power unit 320 includes a vacuum pump 322, which can be communicated with the connection unit 310, and the vacuum pump 322 can extract the slurry in the batching device 100 into the sample preparation mold 200. Further, the vacuum pump 322 can be communicated with the micro-injector 312 of the connection unit 310.
[0107] Further, the power unit 320 also includes a power supply 324. The power supply 324 can be electrically connected to the vacuum pump 322. Specifically, the power supply 324 is electrically connected to the vacuum pump 322 through a wire. The power supply 324 can adjust the vacuum degree of the vacuum pump 322 by adjusting the current and voltage. In this embodiment, the power supply 324 is a DC power supply. It can be understood that the power supply 324 is not limited to a DC power supply, and any power supply 324 that can adjust the vacuum degree of the vacuum pump 322 can be used as the power supply 324 of this embodiment.
[0108] In some embodiments, the power unit 320 further includes a drying bottle 326. The drying bottle 326 can be in communication with the vacuum pump 322, and the drying bottle 326 can be in communication with the connection unit 310, so that the vacuum pump 322 can be in communication with the connection unit 310. Specifically, the drying bottle 326 can be in communication with the micro-injector 312 of the connection unit 310. The drying bottle 326 can be provided to contain impurities and the like in the extraction process to prevent contamination of the power unit 320.
[0109] Furthermore, the power unit 320 further includes a vacuum pressure gauge 328. The vacuum pressure gauge 328 can be connected to the drying bottle 326 to display the vacuum degree in the drying bottle 326. The vacuum pressure gauge 328 can clearly display the vacuum degree in the drying bottle 326.
[0110] Furthermore, the connections among the vacuum pump 322, the drying bottle 326, the micro-injector 312, the Luer connector 3142, the split connector 3144 and the sample preparation mold 200 need to be sealed and connected by high vacuum silicone grease.
[0111] The testing device can test the water-binder ratio of the slurry in the sample preparation mold. Specifically, the testing device is a thermogravimetric analysis device.
[0112] When the test sample preparation system 10 is used to prepare the test sample, the method of use is as follows:
[0113] (1) Connect the power supply 324 and the vacuum pump 322 through a wire, connect the vacuum pump 322 with the drying bottle 326, and connect the vacuum pressure gauge 328 with the drying bottle 326. Connect the drying bottle 326 with one end of the micro-injector 312 through the pipe 316. The other end of the micro-injector 312 is connected to the exhaust port of the sample preparation mold 200 through the Luer connector 3142, the blade ring and the split connector 3144 in sequence.
[0114] (2) Turn on the power supply 324 and the vacuum pump 322, adjust the current and voltage, and obtain a specific vacuum degree through the vacuum pressure gauge 328.
[0115] (3) Insert the sample preparation mold 200 into the batching device 100 containing the standard slurry with a known initial water-binder ratio, and extract the standard slurry into the sample preparation mold 200 through the vacuum pump 322.
[0116] (4) Turn on the thermogravimetric analysis equipment and test the standard slurry in the sample preparation mold 200 to obtain the actual water-binder ratio of the standard slurry.
[0117] (5) Repeat steps (3) and (4) to obtain actual water-binder ratios of multiple standard slurries, and establish a functional relationship between the actual water-binder ratio and the initial water-binder ratio based on the multiple actual water-binder ratios and the multiple initial water-binder ratios.
[0118] (6) According to the water-binder ratio of the test sample to be prepared and the above functional relationship, the water-binder ratio of the sample slurry is obtained.
[0119] (7) Insert the sample preparation mold 200 into the batching device 100 containing the sample slurry, and draw the sample slurry into the sample preparation mold 200 through the vacuum pump 322 to obtain a test sample.
[0120] The above test sample preparation system has at least the following advantages:
[0121] (1) The test sample preparation system is simple and can prepare micron-sized test samples with uniform size.
[0122] (2) The test sample preparation system can make the water-to-binder ratio of the obtained test sample controllable and can be used in X-ray nano-CT scanning tests.
[0123] The following is a specific embodiment:
[0124] Example 1
[0125] The X-ray nano-CT scanning test equipment of this embodiment is Sigray Faastnano XRM developed by Sigray Corporation of the United States, and the light source energy intensity is selected as: monochromatic 8keV characteristic spectral line light (Cu-Kα) produced by high-speed electrons impacting a copper target. In the preparation system of the test sample of this embodiment, the thermogravimetric analysis equipment is German Netzsch 4495F, and the power supply is a DC power supply.
[0126] The raw materials for preparing the test sample in this embodiment include: GSB14-1510 cement standard sample for strength test (main components: tricalcium silicate, dicalcium silicate, tricalcium aluminate; produced by: China Building Materials Science Research Institute, hereinafter referred to as cement standard product) and deionized water. The initial water-cement ratio of the standard slurry is shown in Table 1 below:
[0127] Table 1 Initial water-binder ratio of different standard slurries
[0128] Standard slurry number S1 S2 S3 S4 S5 S6 Initial water-binder ratio 0.4 0.6 0.7 0.8 1.0 1.3
[0129] The preparation process of the test sample of this embodiment is as follows:
[0130] (1) According to the formula When the X-ray energy intensity is 8keV, the X-ray attenuation coefficients of the main components of cement standard, tricalcium silicate, are 0.0160, dicalcium silicate, and tricalcium aluminate, respectively, are 0.0148 and 0.0141. The K value is about 1.4×10 -3 Then according to the Lambert-Beer law formula φ=φ 0 ·exp(-μD), due to φ and φ 0 The ratio of φ to φ must be greater than or equal to 1 / e, so when φ and φ 0 When the ratio is 1 / e, the maximum thicknesses of the main components of the tested cement standard, tricalcium silicate, dicalcium silicate, and tricalcium aluminate, are 62.50 μm, 67.68 μm, and 70.84 μm, respectively.
[0131] Figure 3 This is a graph showing the relationship between the attenuation length and X-ray energy of the main components of cement standard products, tricalcium silicate, dicalcium silicate, and tricalcium aluminate. The attenuation length is the maximum thickness of the test sample, that is, when φ and φ 0 When the ratio is 1 / e, the thickness of the test sample is plotted. To draw the relationship between the attenuation length and the X-ray energy, first use the formula Get the X-ray attenuation coefficient corresponding to each X-ray energy, and then according to φ=φ 0 ·exp(-μD), we get when φ and φ 0 When the ratio is 1 / e, the thickness of the sample (i.e., the attenuation length) is tested to obtain the relationship curve between the attenuation length and the X-ray energy. Figure 3 The curves from top to bottom in the figure correspond to the relationship between the attenuation length and X-ray energy of tricalcium aluminate, dicalcium silicate and tricalcium silicate respectively.
[0132] According to the relationship curve between attenuation length and X-ray energy, at an X-ray energy intensity of 8keV, without considering the porosity of the sample, the maximum thickness allowed for the main components of cement standard, tricalcium silicate, dicalcium silicate, and tricalcium aluminate, is 62.50μm, 67.68μm, and 70.84μm, respectively. It should be noted that the allowable thickness is calculated when the sample is assumed to be one of the main components.
[0133] According to the above, the maximum thickness allowed for tricalcium silicate, dicalcium silicate, and tricalcium aluminate are 62.50μm, 67.68μm, and 70.84μm, respectively. Therefore, the thickness of the sample should be less than 62.50μm. However, since the above three maximum allowable thicknesses are calculated separately and without considering the extreme case of porosity, the actual selection can be slightly larger than 62.50μm. In addition, considering that the sizes of commercially available sample preparation molds are generally 125μm, 65μm, and 25μm. Therefore, considering the above factors comprehensively, the inner diameter of the sample preparation mold is selected to be 65μm.
[0134] Figure 4 This is a graph showing the relationship between the transmittance of tricalcium silicate, dicalcium silicate and tricalcium aluminate and the X-ray energy when the thickness of the main components of cement standard is 65μm. The transmittance is φ and φ 0 ratio. Figure 4 In the figure, the curves from top to bottom correspond to the relationship between the transmittance and X-ray energy of tricalcium silicate, dicalcium silicate and tricalcium aluminate. According to the relationship between transmittance and X-ray energy, at an X-ray energy intensity of 8keV, without considering the porosity of the sample, the transmittance of X-rays when penetrating tricalcium silicate, dicalcium silicate and tricalcium aluminate with a cross-sectional size of 65μm is 35.5%, 38.4% and 40.1% respectively. Since in the Lambert-Beer law formula, φ and φ 0 The ratio is greater than or equal to 1 / e (i.e. 36.7%), and when the thickness is 65μm, the penetration rates of tricalcium silicate, dicalcium silicate, and tricalcium aluminate are all greater than 1 / e, except for tricalcium silicate, which has a slightly lower penetration rate. However, it should be noted that the penetration rate is calculated separately when the sample is assumed to be one of the main components, and the above calculation is based on the extreme case of not considering the porosity, while there is a certain amount of porosity in actual conditions, so the penetration rate of one of them is slightly less than 1 / e. Therefore, the above penetration rate data show that X-ray nanoscanning CT can penetrate samples with a cross-sectional size of 65μm and can detect imaging.
[0135] In this embodiment, according to Figure 3 and Figure 4 Based on the results, a polyetheretherketone (PEEK) tube with an inner diameter of 65 μm was selected as the sample preparation mold.
[0136] Figure 5 The following is a curve showing the relationship between the attenuation length of the sample mold and the X-ray energy when the material of the sample mold is PEEK. Figure 5 The selected PEEK tube with an inner diameter of 65 μm for sample preparation mold has a maximum total diameter of 1180 μm at an X-ray energy intensity of 8 keV. Therefore, when actually selecting a PEEK tube, the total diameter should be less than 1180 μm. The smaller the total diameter of the PEEK tube, the smaller the imaging effect on the sample to be tested. In addition, according to the model of the PEEK tube available on the market, a PEEK tube with a total diameter of 800 μm is selected.
[0137] Figure 6 The material of the sample mold is PEEK, the inner diameter is 65μm, the thickness is 735μm, that is, the total diameter is 800μm, and the relationship between the transmittance of the sample mold and the X-ray energy is shown in the figure. Figure 6 The selected PEEK tube with an inner diameter of 65 μm for the sample preparation mold has a penetration rate of 53.5% when penetrating a 800 μm hollow PEEK tube at an X-ray energy intensity of 8 keV, which meets the requirements of the Lambert-Beer law formula.
[0138] Therefore, according to the above experimental results, a polyetheretherketone (PEEK) tube with an inner diameter of 65 μm, a total diameter of 0.8 mm, and a length of 50 mm was selected as the sample preparation mold of this embodiment.
[0139] (2) Connect a DC power supply and a vacuum pump through a wire, connect the vacuum pump to a drying bottle through a pipeline, connect the vacuum pressure gauge to the drying bottle, connect the drying bottle to one end of a micro-injector through a pipeline, and connect the other end of the micro-injector to a sample preparation mold through a Luer connector, a blade ring, and a split connector in sequence.
[0140] (3) Turn on the DC power supply and vacuum pump. On the premise of sealing the sample injection end of the sample preparation mold, refer to the vacuum pressure gauge and adjust the current and voltage values so that the vacuum value of the vacuum pressure gauge reaches the target value of 2 kPa, which serves as the sampling driving force of the micro-injector.
[0141] (4) The standard slurries S1 to S6 in Table 1 were sequentially drawn into the sample preparation mold, and the drawing time was 3 minutes.
[0142] (5) Measure the weight loss rate curve of the cement standard by thermogravimetric analyzer to establish a baseline weight loss rate curve of the cement standard; measure the weight loss rate curve of the sample making mold by thermogravimetric analyzer to establish a baseline weight loss rate curve of the sample making mold. Then measure the weight loss rate curves of samples S1 to S6 with the sample making mold by thermogravimetric analyzer, and deduct the baseline weight loss rate curves of tricalcium silicate and the sample making mold to obtain the corrected weight loss rate curves of samples S1 to S6, and obtain the actual water-binder ratio of samples S1 to S6. Establish a relationship curve between the actual water-binder ratio and the initial water-binder ratio, such as Figure 7 shown. Figure 7 It is the relationship curve between the actual water-binder ratio and the initial water-binder ratio.
[0143] (6) Set the target water-binder ratio of the test sample to be prepared to 50%, at which point the target water-binder ratio = the actual water-binder ratio. Figure 7 From the relationship curve between the actual water-binder ratio and the initial water-binder ratio, it can be seen that when the vacuum pressure value of the vacuum pressure gauge is set to 2kPa, the prepared water-binder ratio is 0.68.
[0144] (7) Mix the cement standard and water at a water-cement ratio of 0.68 to obtain a sample slurry.
[0145] (8) When the vacuum degree is 2 kPa, the sample slurry is drawn into the sample preparation mold by vacuum extraction. The extraction time is 3 min, and a test sample with an actual water-to-binder ratio of 0.5 is obtained.
[0146] In order to verify the applicability of the preparation method of the test sample of this embodiment, this embodiment performs nanoindentation tests on the samples of the conventional preparation method (prepared on a universal size mold) and the samples prepared by this preparation method, respectively, and compares the components of the hydration products of the two, to assist in proving that the micron-level test samples obtained by quantitatively controlling the water-cement ratio are comparable with the conventional preparation method. It should be added that existing studies have pointed out that the nanoindentation experiment can characterize the three phases of the cement sample through the obtained indentation modulus, namely LS CSH (low-density hydrated calcium silicate gel), HD CSH (high-density hydrated calcium silicate gel) and HD / CH complex. For cement samples prepared under different water-cement ratios, the components of the three phases will also change accordingly. According to the load loading system of this embodiment, the phase here refers to the composite response of the solid phase and the pore phase of the sample, that is, the sample data representing the mechanical properties.
[0147] Two test samples A and B with an actual water-cement ratio of 50% were prepared using standard cement as raw materials, and the curing time was 3 days. Among them, sample B was prepared using the preparation method mentioned above in this embodiment to obtain an initial water-cement ratio of 0.68 and an actual water-cement ratio of 0.5. Sample A was a sample obtained by breaking a test block formed by a cylindrical mold with a diameter of 2 cm and a height of 1 cm, and the initial water-cement ratio was 50%. Nanoindentation tests were carried out on samples A and B respectively, with the number of indentations being 30×10. A load-controlled loading method was adopted, with a peak pressure of 2000μN, a loading time of 5 seconds, a duration of 2 seconds, and an unloading time of 5 seconds. The results of the nanoindentation test are shown in Table 2. Figure 8(a) to Figure 8(c) and Figure 9(a) to Figure 9(c) shown.
[0148] Table 2 shows the volume fractions of each phase obtained after the nanoindentation test of samples A and B respectively, based on the test results, through large sample data processing and Gaussian fitting. Figure 8(a) is the position map of the nanoindentation test of sample A, Figure 8(b) is the data distribution map of the nanoindentation test of sample A, and Figure 8(c) is the Gaussian fitting result map of the large sample data processing of the nanoindentation test of sample A. Figure 9(a) is the position map of the nanoindentation test of sample B, Figure 9(b) is the data distribution map of the nanoindentation test of sample B, and Figure 9(c) is the Gaussian fitting result map of the sample data processing of the nanoindentation test of sample B (including the sample preparation mold). Among them, the test equipment is the HiSilicon TI950 nanoindenter, and the indentation modulus result is automatically obtained by analyzing the loading and unloading curves of the equipment.
[0149] Table 2 Volume fraction of each phase divided by nanoindentation test of sample A and sample B
[0150]
[0151] It can be seen from Table 2, Figure 8(c) and Figure 9(c) that the volume fraction ratio of each phase of the sample prepared by the preparation method of the test sample of this embodiment is basically consistent with that of the sample prepared by the conventional sample preparation method. When some statistical errors are not considered, the ratio of LD CSH to HD CSH is about 3:1. The representativeness of the sample itself is not affected by the preparation method and device of the test sample and the size of the sample.
[0152] The obtained B sample was scanned by the above X-ray nano-CT scanning test equipment. The parameters in the scanning process are: exposure time is 130s, detector merged display pixel is bining2, scanning range is -90°~90°, step length is 0.1°, total duration is 234000s, and the mode used is large field of view mode (Large Field of View), at this time LFOV=80μm, and under bining2, the size of 1 individual pixel can reach 0.04μm. Among them, Figure 10(a) is the image of B sample after three-dimensional reconstruction, and Figure 10(b), Figure 10(c) and Figure 10(d) are 2D slice images of three different directions of the image of B sample after three-dimensional reconstruction (Figure 10(a)). Figure 11(a) and Figure 11(b) are 3D images of B sample after three-dimensional reconstruction of different degrees.
[0153] It can be seen from Figures 10(b), 10(c), 10(d) and 11(a), 11(b) that: 1. The sample shape is a regular cylindrical shape, and as long as the sample preparation mold does not change, the geometric dimensions can be repeatedly achieved; 2. The selected mold has an extremely small X-ray attenuation coefficient, uniform material, and stable quality, so it has a very small effect on the X-ray imaging process of the cementitious material prepared inside it, and almost does not affect the judgment of the results; 3. Due to the "wall effect", an interface transition zone is generated between the internal cementitious material and the sample preparation mold. This transition zone is not generated by the use of this preparation method, but is a phenomenon that will occur when any cementitious sample is prepared by any mold. Therefore, this preparation method can reflect the sample transition zone under actual conventional preparation conditions to a certain extent, and provide multiple research objects by screening the test results.
[0154] The above experimental results all show that the test sample preparation method and preparation system of this embodiment can prepare micron-level test samples, and the test samples have regular shapes and controllable water-to-binder ratios, and can be used in X-ray nano-CT scanning tests.
[0155] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0156] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a test sample, characterized in that: The steps include: A plurality of standard slurries with different initial water-to-binder ratios are prepared using raw materials for preparing test samples, wherein the test samples are gelling materials and the raw materials include solid raw materials and solvents; Placing a plurality of standard slurries with different initial water-binder ratios in a plurality of sample preparation molds respectively, and then testing the actual water-binder ratio of the standard slurries in each of the sample preparation molds, wherein the inner diameter of the sample preparation mold is in the micrometer order; According to the plurality of actual water-binder ratios and the plurality of initial water-binder ratios, establishing a functional relationship between the actual water-binder ratio and the initial water-binder ratio; Calculating the initial water-binder ratio of the test sample according to the functional relationship and the actual water-binder ratio of the test sample; According to the initial water-binder ratio of the test sample, the raw materials are prepared into a sample slurry; and The sample slurry is placed in the sample preparation mold to obtain the test sample.
2. The method for preparing a test sample according to claim 1, characterized in that: The test sample is a sample for X-ray nano CT scanning test.
3. The method for preparing a test sample according to claim 2, characterized in that: The inner diameter of the sample preparation mold is smaller than the maximum thickness of the test sample that can be tested by the X-ray nano CT scanning test.
4. The method for preparing a test sample according to claim 3, characterized in that: Before the step of placing the plurality of standard slurries with different initial water-binder ratios in a plurality of sample preparation molds, the method further includes a step of determining the maximum thickness of the test sample that can be tested by the X-ray nano CT scanning test, wherein the step of determining the maximum thickness includes: According to the density and effective atomic number of the solid raw material, and the X-ray energy intensity used by the light source of the X-ray nano-CT scanning test, according to the formula , calculate the X-ray attenuation coefficient of the solid raw material, wherein μ represents the X-ray attenuation coefficient, ρ represents the density, Z represents the effective atomic number, E represents the X-ray energy intensity, and K is a constant; According to the formula , obtain the maximum thickness of the test sample that can be tested by the X-ray nano CT scanning test, wherein φ represents the intensity of emitted photons, φ0 represents the intensity of incident photons, the ratio of φ to φ0 is greater than or equal to 1 / e, and D is the thickness of the test sample.
5. The method for preparing a test sample according to claim 1, characterized in that: The step of establishing a functional relationship between the actual water-binder ratio and the initial water-binder ratio according to the plurality of actual water-binder ratios and the plurality of initial water-binder ratios comprises: According to the plurality of actual water-binder ratios and the plurality of initial water-binder ratios, establishing a relationship curve between the actual water-binder ratio and the initial water-binder ratio; The relationship curve is linearly fitted to obtain the functional relationship between the actual water-binder ratio and the initial water-binder ratio.
6. The method for preparing a test sample according to claim 1, characterized in that: In the step of testing the actual water-binder ratio of the standard slurry in each of the sample preparation molds, a thermogravimetric method is used to test the actual water-binder ratio of the standard slurry in each of the sample preparation molds.
7. The method for preparing a test sample according to claim 1, characterized in that: In the step of placing the multiple standard slurries with different initial water-to-binder ratios in multiple sample preparation molds respectively, vacuum extraction is performed so that the multiple standard slurries with different initial water-to-binder ratios are placed in multiple sample preparation molds respectively, and the vacuum degree during the vacuum extraction process is the same.
8. The method for preparing a test sample according to claim 1, characterized in that: The material of the sample making mold is polymer.
9. A test sample preparation system, characterized in that: The method for preparing a test sample according to any one of claims 1 to 8, wherein the test sample is a sample for an X-ray nano-CT scanning test, and the preparation system comprises: A batching device, used for holding slurry; A sample preparation mold, used to hold the slurry, and the inner diameter of the sample preparation mold is micrometer-level and smaller than the maximum thickness of the test sample that can be tested by the X-ray nano-CT scanning test, and the sample preparation mold is a polyimide mold or a polyetheretherketone mold; A material transfer device, used for transferring the slurry in the batching device to the sample preparation mold; and A testing device is used to test the water-binder ratio of the slurry in the sample preparation mold.
10. The test sample preparation system according to claim 9, characterized in that: The sample preparation mold is connected to the batching device, and the material transfer device includes a connecting unit and a power unit. The connecting unit is connected to the sample preparation mold, and the power unit is connected to the connecting unit, so that the slurry in the batching device is extracted into the sample preparation mold.
11. The test sample preparation system according to claim 10, characterized in that: The sample preparation mold has a feed port and an air suction port, the feed port is connected to the batching device, the connection unit includes a micro-injector and a connector detachably connected to the micro-injector, the micro-injector is connected to the power unit, the connector is connected to the air suction port, and when the connector is connected to the air suction port, the connector is sealed and connected to the sample preparation mold so that the slurry in the batching device is extracted into the sample preparation mold.
12. The test sample preparation system according to claim 10, characterized in that: The power unit comprises a vacuum pump, which is communicated with the connection unit so that the slurry in the batching device is drawn into the sample preparation mold.
Citation Information
Patent Citations
Determination method of cement concrete mixture water-cement ratio
CN103217515A
Foam concrete sample production apparatus abutted to indoor rock soil mechanical test machine, and method thereof
CN106053183A
Test sample preparation system
CN210427165U